Guard Labor: An Essay in Honor of Pranab Bardhan - Samuel Bowles; Arjun Jayadev (University of Massachusetts, Department of Economics, 2004)
We explore the exercise of power in perpetuating status quo institutions. We give empirical examples of the economic importance of power and offer a definition of this elusive term. We then investigate the role of power in a modern capitalist economy, borrowing ideas from the classical economists (unproductive labor, profit-driven investment), Marx (the labor-disciplining effect of unemployment) and the contemporary theory of incomplete contracts(the role of monitoring and enforcement rents). Our model suggests that a significant portion of an economy's productive potential may be devoted to the exercise of power and to the perpetuation of social relationships of domination and subordination. We then measure these resources in labor units using the concept of guard labor, finding it to be a significant and growing fraction of the U.S. labor force. We also document substantial cross national differences in the extent of guard labor and the strong statistical association between the extent of income inequality and the fraction of the labor force that is constituted by guard labor. We close with some speculations concerning the role of guard labor in the process of economic development and how economies might function better with more carrot and less stick.
Keywords: O17; P50; N32; B52; K42; 330; enforcement rents; institutions; guard labor; supervision; social conflict; labor-management